Access to Justice Due to the Covid-19 Pandemic - Голубєва, Неллі Юріївна; Голубєва, Н. Ю.; Голубева, Нелли Юрьевна; Golubeva, Nelli; Holubieva, Nelli Yu.; Бут, Ілля Олександрович; Бут, І.О.; Бут, Илья Александрович; But, Illia O.; Прохоров, Павло Анатолійович; Прохоров, П. А.; Прохоров, Павел Анатольевич; et al. (Los Hemisferios University, 2020)
The coronavirus pandemic (Covid-19) has caused many challenges to democracy around the world. Under the new conditions, states must implement effective quarantine measures, as well as take decisions that justifiably and least restrict human rights. In this pandemic context of many restrictions, it is important to pay attention to ensuring access to justice and to investigate its level of security. The article aims to analyze the right of access to justice in the context of the Covid-19 pandemic, both in Ukraine and other countries. The subject of the study is the public relations that arise during the exercise of the right of access to justice in the pandemic context. The research methodology includes a scope of methods, the most important of which are the dialectical method, the analysis method, the synthesis method, the comparative method, the induction method, and the deduction method. As a result of the study, an analysis of the right of access to justice in the context of Covid-19 has been made. The main conclusion of this study is that the Covid-19 pandemic has clearly shown that the transition to online technology and other innovations in the judiciary has so far been too slow. On the other hand, in the context of ensuring access to justice the pandemic has become a kind of trigger for the rapid development and implementation of the latest innovative technologies in the field of access to justice.

Пандемія коронавірусу (Covid-19) спричинила багато викликів демократії у всьому світі. За нових умов держави повинні застосовувати ефективні карантинні заходи, а також приймати рішення, які є виправданими та найменш обмежують права людини. У цьому пандемічному контексті багатьох обмежень важливо приділити увагу забезпеченню доступу до правосуддя та дослідити рівень його безпеки. Стаття має на меті проаналізувати право на доступ до правосуддя в контексті пандемії Covid-19 як в Україні, так і в інших країнах. Предметом дослідження є суспільні відносини, що виникають під час реалізації права на доступ до правосуддя в умовах пандемії. Методологія дослідження включає коло методів, найважливішими з яких є діалектичний метод, метод аналізу, метод синтезу, порівняльний метод, метод індукції та метод дедукції. В результаті дослідження було проведено аналіз права на доступ до правосуддя в контексті Covid-19. Основним висновком цього дослідження є те, що пандемія Covid-19 чітко продемонструвала, що перехід до онлайн-технологій та інших нововведень у судовій системі досі був занадто повільним. З іншого боку, в контексті забезпечення доступу до правосуддя пандемія стала своєрідним пусковим механізмом для швидкого розвитку та впровадження новітніх інноваційних технологій у галузі доступу до правосуддя.

Пандемия коронавируса (Covid-19) вызвала множество вызовов демократии во всем мире. В новых условиях государства должны применять эффективные карантинные меры, а также принимать оправданные решения и наименее ограничивающие права человека. В этом пандемическом контексте множества ограничений важно уделять внимание обеспечению доступа к правосудию и исследовать уровень его безопасности. Статья направлена ​​на анализ права на доступ к правосудию в контексте пандемии Covid-19 как в Украине, так и в других странах. Предметом исследования являются связи с общественностью, возникающие при реализации права на доступ к правосудию в контексте пандемии. Методология исследования включает набор методов, наиболее важными из которых являются диалектический метод, метод анализа, метод синтеза, сравнительный метод, метод индукции и метод дедукции. В результате исследования был проведен анализ права на доступ к правосудию в контексте Covid-19. Главный вывод этого исследования заключается в том, что пандемия Covid-19 ясно показала, что переход к онлайн-технологиям и другим инновациям в судебной системе до сих пор был слишком медленным. С другой стороны, в контексте обеспечения доступа к правосудию пандемия стала своеобразным спусковым крючком для стремительного развития и внедрения новейших инновационных технологий в сфере доступа к правосудию.
Golubeva N. Access to Justice Due to the Covid-19 Pandemic / N. Golubeva, I. But, P. Prokhorov // Ius Humani. Law Journal. – Los Hemisferios University, 2020. – V. 9(2). – P. 47-64.
Keywords: Access to Justice; Rights and Freedoms; Quarantine Restrictions; Covid-19; Judicial Protection; доступ до правосуддя; права і свободи; карантинні обмеження; пандемія Covid-19; судовий захист; доступ к правосудию; права и свободы; карантинные ограничения; пандемия Covid-19; судебная защита; Research Subject Categories::LAW/JURISPRUDENCE